İlköğretim 4. ve 5. Sınıf Öğrencilerinin Sosyal Bilgiler Dersine Yönelik Algılarının İncelenmesi - ÇİFTÇİ, Barış; KAYA, Mehmet Tamer (My University, 2012)
Bu araştırma, ilköğretim 4 ve 5. sınıf öğrencilerinin Sosyal Bilgiler dersine yönelik tutumlarını ve tutumlarını etkileyen değişkenleri belirlemek amacıyla yapılmıştır. Çalışmada survey yöntemi kullanılmıştır. Çalışma, betimsel bir çalışmadır. Sınırlandırılmış evren yöntemiyle Afyonkarahisar il merkezindeki okullar, üç alt evrene ayrılmış ve ölçek, bu okullardaki 272 öğrenciye uygulanmıştır. Uygulama sonrası yapılan analizlerde öğrencilerin cinsiyet, sınıf, anne-baba eğitim durumu ve aile gelir düzeyi bakımından tutum ölçeğine verilen cevaplar arasında anlamlı farklılıklar tespit edilmiştir.
Analysis of 4th and 5th Graders’ Perceptions of Social Studies
Education firstly begins in family, and continues with formal education as a fact which should be continued through life. But, the basic foundations of education need to be taken into consideration to be efficient. Hence, primary schools considering basic foundations of education shape our children’s future. Students’ positive attitudes toward a course might affect their success in that course. One of the important goals of social studies course is to grow effective and productive citizens. Children during the first years of their lives by effective teaching of social studies will later take place in society as responsible and sensitive citizens. In learning, students’ interests and needs, readiness levels, attitudes and values are important in terms of their attaining course objectives.This study aims to determine 4th and 5th graders’ attitudes toward social studies course and whether those differ on several variables. It is a survey research design. The sample of this descriptive study consists of three schools in Afyonkarahisar, Turkey.
Keywords: sosyal bilgiler, birinci kademe öğrencilerinin tutumları